WHY DID THE CATHOLIC MISSIONARIES FAIL TO CONVERT THE ARMENIAN AND GEORGIAN COMMUNITY OF THE SAFAVID EMPIRE IN THE 17th CENTURY? - Heydarli, Gunay (PEOPLE: International Journal of Social Sciences, 2019)
In the early modern period the Protestant Reformation weakened the Roman Catholic Church and it lost its influence over Europe. The Church turned its policy to the East to propagate the faith. For nearly a century, the missionaries were represented in the Safavid provinces and attempted to win the Eastern Christian Population for the Catholic Church. On the other hand,with the flow of Catholic missionaries caused the increase of intercultural and interreligious exchanges. This paper examines the Catholic missionaries’motives to bring the Safavids’ Eastern Christian Community under papal jurisdiction as well as the reception that the Safavid rulers, Armenian Church and Georgian Church offered vis-a-vis this group. The aim of the study is to investigate the missionaries’ attempts to create a ‘fifth column’ by proselytizing the Eastern Christian Community in the Safavid territories.